2020
DOI: 10.30699/ijmm.14.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus: Scientometrics of 50 Years of Global Scientific Productions

Abstract: Background: Scientometrics studies are one of the most efficient methods of quantitative evaluation of the scientific outputs of valuable information and citation databases for understanding and observing the status of scientific publications in different subject areas. The main aim of this article was to study the 50 years of Coronavirus scientific publications in the world. Materials & Methods: This applied research was carried out using scientometrics methods and an analytical approach. The statistical popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
7
18
0
Order By: Relevance
“…The potency of camostat against SARS-CoV-2 was ~100-fold greater in our Caco-2 cell assay than in a previous study using Vero-E6 cells 23 but similar to the results of another study with the same virus and cell line 24 , as well as studies of MERS-CoV and SARS-CoV using Calu-3 cells 25 , 26 . Likewise, the potency of nafamostat against SARS-CoV-2 in our Caco-2 cell assay was >500-fold greater than in previous studies using Vero-E6 cells 27 , 28 but similar to the results of a previous study of MERS-CoV cytopathicity against Calu-3 cells 26 . Papaverine was eight-fold more potent against SARS-CoV-2 (in Caco-2 cells) than against MERS-CoV (in BHK-21 cells) 29 whereas cetylpyridinium showed similar potency in both assays 29 .…”
Section: Technical Validationsupporting
confidence: 86%
“…The potency of camostat against SARS-CoV-2 was ~100-fold greater in our Caco-2 cell assay than in a previous study using Vero-E6 cells 23 but similar to the results of another study with the same virus and cell line 24 , as well as studies of MERS-CoV and SARS-CoV using Calu-3 cells 25 , 26 . Likewise, the potency of nafamostat against SARS-CoV-2 in our Caco-2 cell assay was >500-fold greater than in previous studies using Vero-E6 cells 27 , 28 but similar to the results of a previous study of MERS-CoV cytopathicity against Calu-3 cells 26 . Papaverine was eight-fold more potent against SARS-CoV-2 (in Caco-2 cells) than against MERS-CoV (in BHK-21 cells) 29 whereas cetylpyridinium showed similar potency in both assays 29 .…”
Section: Technical Validationsupporting
confidence: 86%
“…Results of some previous studies were similar to this study, which exhibited that the United States was the most productive country in different areas of research, such as like Carpal Tunnel Syndrome, Coronavirus, Middle East Respiratory Syndrome (MERS), m-health, Sudden Infant Death Syndrome, and regulatory T-cell ( Bonilla-Aldana et al , 2020 ; Danesh & Ghavidel, 2020 ; Menezes et al, 2020 ; Ram, 2019 ; Ram, 2020 ; Sweileh et al , 2017 ; Wang et al , 2016 ; Zongyi, et al , 2016 ; Zyoud, 2016 ).…”
Section: Resultssupporting
confidence: 88%
“…Our analysis showed that nine out of the top ten contributing organizations were academic institutions and most of them (six) were based in the United States, which also confirmed the results of the country-wise analysis. Analogous results were exhibited during earlier studies, which found that universities contributed much of the research related to MERS, coronavirus, and regulatory T-cells ( Danesh & Ghavidel, 2020 ; Ram, 2020 ; Wang et al , 2016 ; Zongyi, Dongying & Baifeng, 2016 ).…”
Section: Resultssupporting
confidence: 83%
“…In the coronavirus area, the number of scientometric and bibliometric studies can be mentioned. For example, Danesh and Ghavidel evaluated the scientific publications of the last half-century on coronavirus using scientometric methods (Danesh and Ghavidel, 2020). Bonilla-Aldana et al also carried out the bibliographic analysis of coronaviruses (Bonilla-Aldana et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the objectives of studies related to text mining is to identify the topics of scientific texts, evaluate these topics and apply the visualization tools for presenting each topic and the relationship between them as an approach to assist users in determining topics (Salloum et al , 2018). Currently, along with the second wave of COVID-19 outbreaks in many countries around the world, medical scientists are conducting significant research projects and clinical trials on the ways of prevention, treatment, and the development of vaccines and effective medicines to combat and eliminate COVID-19 and the results of their studies are published in peer-reviewed journals (Danesh and Ghavidel, 2020). Therefore, the evaluation and analysis of published documents related to coronavirus by applying text mining techniques are of particular importance for researchers, policymakers and medical planners at the international level and highlights the need for such research papers.…”
Section: Introductionmentioning
confidence: 99%